2015
DOI: 10.1109/lcomm.2015.2418261
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Complexity Linear Programming Decoding Based on ADMM for LDPC Codes

Abstract: The Euclidean projection onto check polytopes is the most time-consuming operation in the linear programming (LP) decoding based on alternating direction method of multipliers (ADMM) for low-density parity-check (LDPC) codes. In this letter, instead of reducing the complexity of Euclidean projection itself, we propose a new method to reduce the decoding complexity of ADMM-based LP decoder by decreasing the number of Euclidean projections. In particular, if all absolute values of the element-wise differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…from auxiliary variables introduced to the three-variables parity-equations. • Compared with the state-of-the-art works [31]- [33], [35], [37]- [39] and [41]- [44], the proposed ADMM algorithm is free of the complex Euclidean projection on each check polytope. From (17), it is easy to see that updating the variables in z only requires a simple Euclidean projection onto the positive quadrant.…”
Section: B Admm Algorithm Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…from auxiliary variables introduced to the three-variables parity-equations. • Compared with the state-of-the-art works [31]- [33], [35], [37]- [39] and [41]- [44], the proposed ADMM algorithm is free of the complex Euclidean projection on each check polytope. From (17), it is easy to see that updating the variables in z only requires a simple Euclidean projection onto the positive quadrant.…”
Section: B Admm Algorithm Frameworkmentioning
confidence: 99%
“…Authors in [36] simplified the check projection operation by jointly using uniform quantization and look-up tables. Moreover, a projection reduction method [37] and two different approaches based on node-wise scheduling and horizontal-layered scheduling in [38] and [39] respectively were proposed to reduce the decoding complexity by decreasing the number of projections. Furthermore, authors in [40] introduced an efficient ADMM-based LP decoding algorithm, which can eliminate the expensive projection operation onto the check polytope.…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al modified penalization to improve error-rate performance of irregular LDPC codes [24]. Finally, Wei et al implemented ADMM-LP avoiding projections when possible [25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the projection on parity check polytope is the most computationally intensive part of the whole decoding process. To deal with the problem of high computational complexity of projection, Wei et al proposed the reduction of useless projection in [2]. Besides, Jiao et al suggested increasing the projection efficiency using the look-up table to reduce the projection operation [3].…”
Section: Introductionmentioning
confidence: 99%